Body Donation after Medically Assisted Death: An Emerging Consideration for Donor Programs. Issue 4 (28th March 2019) - Wainman, Bruce C.; Cornwall, Jon
Abstract : Around the world, the recent introduction of assisted death laws has meant that undertaking medical assistance in dying (MAID) is now an option for some persons wishing to end their life. Some of these people donate their bodies to medical science, and by doing so have created a new route from which donor programs can now receive bodies. Such donations have also illuminated a myriad of novel ethical questions. This article considers the emotive and controversial topic of MAID in relation to body donation, describing the experiences of McMaster University, Canada, where several MAID body donors have been received by the anatomical donor program. It provides background on the development and implementation of MAID in Canada, and describes the experience of staff and students at McMaster to MAID donations. It also explores the relevance of MAID to body donation programs, and discusses several of the ethical challenges facing body donation programs who may encounter MAID body donors. These include the appropriateness of accepting MAID donors, issues with informed consent, the effect of personal engagement with MAID donors, information sharing around MAID donations, governance issues, and negative historical parallels between MAID and euthanasia. Suggestions on how to manage MAID body donation focus on how issues affecting institutions, faculty, and students may be approached utilizing appropriate transparency and communication, some of which may facilitate student professional development around the topic of MAID. It is also suggested that the development of ethically appropriate guidelines on MAID body donations may positively guide the anatomical community.